Melindungi Permata Biru: Kolaborasi Masyarakat Sumbawa dalam Konservasi Penyu dan Habitat Terumbu Karang - Medina Arrahman; Yanti Meriska (Journal of Community Development and Empowerment, 2026)
The destruction of coastal ecosystems on Sumbawa Island due to destructive activities threatens the conservation of sea turtles and coral reef habitats known as the "Blue Jewel." This community service activity aims to increase the awareness, knowledge, and active participation of local communities in integrated maritime conservation efforts. The implementation methods used included interactive socialization, sea turtle nest monitoring training, coral reef rehabilitation technique workshops (coral transplantation), and the formation of a Community Surveillance Group (Pokmaswas). The results of the activity showed an 85% increase in the partner community's understanding of the importance of preserving marine ecosystems. Through this collaboration, 200 new coral nubbins were successfully planted in the conservation area, and a joint commitment was agreed upon for coastal protection patrols against sea turtle egg poaching. The success of this program proves that a community-based conservation approach is effective in creating sustainable ecosystem resilience. For the sustainability of the program, stronger synergy with the local government is required in providing local regulations to safeguard Sumbawa's "Blue Jewel" for future generations.